Anatomy of air entrapment in drop impact on a solid surface. (September 2021) - Wu, Zhenlong; Cao, Yihua; Yao, Yufeng
Highlights: The whole air entrapment process is directly simulated with very high fidelity and resolution. A mesh topology is specially designed for capturing the air bubble with low computational cost. Each phase of the air entrapment evolution process is characterized in detail. A new cognition of vortex ring evolution is proposed to explore the underlying physical mechanism. Abstract: When a drop impacts on a solid surface, a thin air film is entrapped first and later evolves into a spherical air bubble at the center inside the drop. The problem involves several complex physical processes, including two-phase fluid flow interactions, moving and deforming interfaces in space and time. In this paper, we dissect the whole air entrapment and evolution process from drop release at a certain height above the substrate to finally a spherical air bubble formation by direct numerical simulation. A detailed quantitative analysis of the various dynamic phenomena occurring at different stages is performed. The complex physical phenomena revealed by current high-fidelity numerical simulations are validated qualitatively against theoretical estimations and previous experimental observations, followed by quantitative comparisons with the theories and available experiments for the dimple, kink and air film. Finally, a new cognition of vortex ring evolution is proposed to explore further insights into the underlying physical mechanisms associated with the evolution of the entrapped air film in liquid-solid impact. Graphical abstract: Image, graphical abstract